Pharmaceutical Cold Chain Using Blockchain 3.0 - Padmavathi, U.; Rajagopalan, Narendran (International Journal of Psychosocial Rehabilitation, 2024)
The term cold chain or cool chain refers to the process of preserving vaccines at consistent temperatures from the manufacturing place along the supply chain to the point of use. Vaccines need to be stored in the temperature range of 2–8 °C in order to maintain their potency. If the cold chain is broken even for a shorter period of time, then it could result in impotent drug, product wastage, and money wastage, and there will be a need for revaccination. Monitoring and managing the cold chain is an expensive process. According to Pharmaceutical Commerce’s Annual Biopharma Cold Chain Sourcebook, by 2021, the worth of pharma cold chain would be $16.6 billion. Moreover, the U.S. survey suggested that 1% to 5% of vaccines are wasted due to breaks in the cold chain, and it could cost about $31 million. Cold chain management suffers from various problems such as lack of documentation, lack of continuous monitoring, temperature issues, and security issues. The perfect solution that comes to rescue the cold chain problem is blockchain. This paper first discusses the cold chain, its importance, and the various problems associated with it. It also sheds light on blockchain technology, its versions, and how blockchain could solve the problems of the cold chain. This paper proposes an architectural framework that measures and records temperature of cold chain pharmaceutical products using Blockchain 3.0